PROBLEMATIKA PEMBANGUNAN PARIWISATA BUDAYA DI DESA PULAU MARINGKIK - Putraji, Lalu Muhammad Guguh; Furkan, Lalu Muhammad; Uswanti, Bimantari Putri; Wandikbo, Indikum Nyamuk; Fadli, Muhammad; Zubaidi, Mayoni; Estiana, Elsa; Jumiarti, Jumiarti; Alivia, Fajri Atullah; Olvyana, Annsia; Ardiansyah, Ardiansyah; Asry, Nur (Universitas Mataram, 2023)
Cultural tourism or